2007
DOI: 10.1139/h07-119
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory constraints and dyspnea during exercise in chronic obstructive pulmonary disease

Abstract: Dyspnea (respiratory difficulty) and activity limitation are the primary symptoms of chronic obstructive pulmonary disease (COPD) and progress relentlessly as the disease advances, contributing to reduced quality of life. In COPD, the mechanisms of dyspnea are multifactorial, but abnormal dynamic ventilatory mechanics are believed to play a central role. In flow-limited patients with COPD, dynamic lung hyperinflation (DH) occurs during exercise and has serious sensory and mechanical consequences. In several st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 101 publications
(181 reference statements)
0
28
0
2
Order By: Relevance
“…10,12,18,37 Considerable evidence has accumulated that exercise-induced dynamic lung hyperinflation may represent an important factor contributing to exercise intolerance in subjects with COPD. 12,18 Previous studies demonstrated that dynamic hyperinflation can be measured after submaximal exercise such as 6MWT in subjects with COPD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,12,18,37 Considerable evidence has accumulated that exercise-induced dynamic lung hyperinflation may represent an important factor contributing to exercise intolerance in subjects with COPD. 12,18 Previous studies demonstrated that dynamic hyperinflation can be measured after submaximal exercise such as 6MWT in subjects with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,18,37 Considerable evidence has accumulated that exercise-induced dynamic lung hyperinflation may represent an important factor contributing to exercise intolerance in subjects with COPD. 12,18 Previous studies demonstrated that dynamic hyperinflation can be measured after submaximal exercise such as 6MWT in subjects with COPD. 8,11,26 Accordingly, in the present study, dynamic hyperinflation could be observed, as reflected by a significant decrease in inspiratory capacity and inspiratory vital capacity as well as an increase in FRC, RV, and RV%TLC after the 6MWT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This disparity leads to intense dyspnea sensation that is the symptom-limiting exercise in a large fraction of patients with chronic lung diseases (155,168). The factors contributing to decreased ventilatory capacity or increased ventilatory requirement/workload are described later in brief.…”
Section: Ventilatory Constraintsmentioning
confidence: 99%
“…1A) (145,212). Combined data from clinical studies (155,180,221) have revealed that the frequency of exerciselimiting symptoms during constant-load exercise in a cohort of 403 patients with moderate to severe COPD was by approximately 60% accountable to intolerable dyspnea sensations, whereas leg discomfort alone or in combination with dyspnea accounted for the remaining approximately 40%.…”
Section: Exercise-limiting Factors In Patients With Chronic Obstructimentioning
confidence: 99%